Di-tert-butyl 2,2 `-[9H-fluorene-9,9-diylbis(p-phenyleneoxy)]diacetate - Shah, K.; Yousuf, S.; Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
In the title molecule, C(37)H(38)O(6), the non-fused C atom belonging to the five-membered ring of the fluorene system is connected to two p-phenylene rings, the rings opening up the C(aryl)-C-C(aryl) angle to 113.1 (1)degrees. The four-atom -O-CH(2)-C(= O)-O- chain between the p-phenylene ring and the tert-butyl group assumes a more regular W-shaped conformation for one substituent [O-C-C-C torsion angle = 171.9 (2)degrees] but a less regular W-shaped conformation for the other [torsion angle = 147.4 (2)degrees].